Physiological determinants of ultramarathon trail-running performance - Coates, A. M.; Berard, J. A.; King, T. J.; Burr, J. F. (International Journal of Sports Physiology and Performance, 2021)
Context: The physiological determinants of ultramarathon success have rarely been assessed and likely differ in their contributions to performance as race distance increases.